Effects of oral micellized natural vitamin E (d-α-tocopherol) v. synthetic vitamin E (dl-α-tocopherol) in feed on α-tocopherol levels, stereoisomer distribution, oxidative stress and the immune response in piglets. (18th February 2014) - Amazan, D.; Cordero, G.; López-Bote, C. J.; Lauridsen, C.; Rey, A. I.
<x content-type="archive" xml:space="preserve">Abstract</x> This study evaluated the strategy of supplementing oral micellized natural vitamin E (d-α-tocopherol) to either piglets and/or sows on α-tocopherol concentrations in piglets serum and tissues after weaning. One first experiment tested the influence of the vitamin E supplementation source (natural form in water v. the synthetic form in feed) and dose administered to piglets and/or sows on serum α-tocopherol concentration, α-tocopherol stereoisomer accumulation, antioxidant capacity and immune response of weaned piglets. A second experiment studied the effect of sow source and dose vitamin E supplementation on some of these parameters in piglets. Oral supplementation to sows with natural vitamin E as a micellized form (d-α-tocopherol) at the lowest dose produced a similar concentration of α-tocopherol in serum at days 2, 14 and 28 postpartum to those supplemented with threefold higher dose of the synthetic form in feed. At day 39 of age, neither piglet supplementation source nor dose significantly affected α-tocopherol accumulation in the serum, muscle, subcutaneous fat or liver. Those piglets from sows supplemented with the micellized alcohol form had higher RRR-α-tocopherol stereoisomers (P<0.001) and lower (P<0.001) RRS- RSS- and RSR-α-tocopherol, at day 39 of age than those from sows supplemented with the synthetic form. A predominant importance of sow over piglet vitamin E supplementation was observed on stereoisomer distribution in piglets. Low doses of oral natural vitamin E supplementation to sows or piglets did not increase the oxidative stress of piglets when compared with the use of the synthetic form in feed. Immunoglobulin levels in piglet serum at day 39 were not affected by natural vitamin E supplementation at low doses in drinking water of piglets or sows when compared with the synthetic form in feed. IgA tended to be higher (P=0.145) at day 39 in piglets supplemented with natural vitamin E when compared with those supplemented with the synthetic form. Low doses of oral micellized natural vitamin E supplementation to sows is an interesting feeding strategy, when compared with the use of high doses of the synthetic form in feed, because it results in similar α-tocopherol concentrations, allows a predominant –R stereoisomer distribution in piglets and also maintains their oxidative status in vivo.